Services in Doha : What’s on the Table? - Gootiiz, Batshur; Mattoo, Aaditya (2012)
Services trade reform matters, but what is Doha doing about it? It has been hard to judge, because of the opaqueness of services policies and the opaqueness of the request-offer negotiating process. This paper attempts to assess what is on the table. It presents the results of the first survey of applied trade policies in the major services sectors of 56 industrial and developing countries. These policies are then compared with these countries' Uruguay Round commitments in services and the best offers that they have made in the current Doha negotiations. The paper finds that at this stage, Doha promises greater security of access to markets but not any additional liberalization. Uruguay Round commitments are on average 2.3 times more restrictive than current policies. The best offers submitted so far as part of the Doha negotiations improve on Uruguay Round commitments by about 13 percent but remain on average 1.9 times more restrictive than actual policies. The World Trade Organization's Hong Kong Ministerial had set out ambitious goals for services but the analysis here shows that much remains to be done to achieve them.